Społeczne preferencje w zakresie wypoczynku w zależności od wyglądu lasu na przykładzie lasów miejskich Tarnowa - Mandziuk, Agnieszka; Fornal-Pieniak, Beata (Leśne Prace Badawcze, 2024)
The aim of the study was to determine the social preferences for recreation in the urban forests of Tarnów (Polish: “lasy miejskie Tarnowa”, LMT) depending on their appearance. The article also determines the frequency of visits and the amount of compensation for not visiting the urban forests depending on their appearance. To investigate this, we conducted 309 surveys in the LMT area in the period July-August 2020. For this purpose, respondents were presented with four options (I-IV) describing different types of forests, from simple to complex structures with recreational infrastructure. Based on surveys, the sociological characteristics of the respondents, the frequency of visits to the LMT and the relationship between the appearance of the forest and the frequency of visits, as well as the level of Willingness To Accept (WTA) were determined. The WTA model was created based on the compensation amounts given. The responses of 309 people who visited the LMT were used for the analysis. Most people visited the urban forests once a week and once a month. Respondents preferred to visit forests with complex structure and recreational infrastructure. The more complex the forest structure and the greater the recreational infrastructure, the more frequently the urban forests were visited and the greater the relationship between the WTA level and the forest appearance. The average value of compensation was PLN 88, the maximum PLN 300, and the most frequently reported amount was PLN 100. The declared level of compensation received was 85%. When choosing a forest for recreation, a clear division of social preferences was found depending on its appearance. One group of respondents chose forests with little undergrowth and ground vegetation, while the second group of respondents preferred multi-storey, multi-species forests with recreational infrastructure. The more complex the forest structure, the greater the respondents’ willingness to receive compensation.